2016
DOI: 10.1021/acs.orglett.6b02999
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Multicomponent Reaction (MCR) of Propargylic Carbonates with Isocyanides

Abstract: A palladium-catalyzed multicomponent reaction (MCR) of propargylic carbonates with isocyanides is reported. Remarkably, the orderly insertion of isocyanides affords two types of valuable N-heterocyclic products (Z)-6-imino-4,6-dihydro-1H-furo[3,4-b]pyrrol-2-amines and (E)-5-iminopyrrolones in high yields. Systematic analysis of the reaction conditions indicates that the selectivity of these N-heterocyclic products can be controlled by ligands and temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…In an oxygen isotope‐labeling experiment, [O 18 ]‐ 1 a and 2 a was used to afford [O 18 ]‐ 3 a , suggesting a migratory step occurred (Scheme 2, eq 3). In addition, another isotope experiment also demonstrated that no O 18 was incorporated into the resulting product 3 a when H 2 O 18 served as the third component (Scheme 2, eq 4), thus ruling out the possibility of water as oxygen source [21] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an oxygen isotope‐labeling experiment, [O 18 ]‐ 1 a and 2 a was used to afford [O 18 ]‐ 3 a , suggesting a migratory step occurred (Scheme 2, eq 3). In addition, another isotope experiment also demonstrated that no O 18 was incorporated into the resulting product 3 a when H 2 O 18 served as the third component (Scheme 2, eq 4), thus ruling out the possibility of water as oxygen source [21] …”
Section: Methodsmentioning
confidence: 99%
“…In addition, another isotope experiment also demonstrated that no O 18 was incorporated into the resulting product 3 a when H 2 O 18 served as the third component (Scheme 2, eq 4), thus ruling out the possibility of water as oxygen source. [21] In the presence of optimal conditions, a gram-scale synthesis was conducted with propargylic pivalate 1 a (3 mmol, 0.86 g) and isocyanide 2 a (6 mmol, 0.78 g), affording 3 a in 63% yield (1.04 g) (Scheme 3, eq 1). Treatment of 3 a with Pd/C in ethanol at room temperature for 8 h led to double bond reduction and delivered compound 9 in 62% yield (Scheme 3, eq 2).…”
Section: Communicationsmentioning
confidence: 99%
“…Using isocyanide as C1N1 unit, Jiang and Wu et al [128] reported a palladium-catalyzed multicomponent reaction for the synthesis of pyrrole derivatives from propargylic carbonates and isocyanides (Scheme 91). This reaction Scheme 91 Palladium-promoted cyclization between propargylic carbonates and isocyanides started with the formation of allene intermediate, which went through isocyanide insertion and three consecutive addition steps to produce key intermediate for final cyclization.…”
Section: Scheme 90 Cyclization Of Alkylnitriles Arylalkynes and Me-otfmentioning
confidence: 99%
“…Recently, we developed novel palladium-catalyzed diarylation reactions of isocyanides 2 [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] using triarylbismuthines 1 and tetraarylleads 4 ( Scheme 1 ). The use of BiAr 3 1 result in α -diimines 3 being selectively obtained ( Scheme 1 a) [ 42 ].…”
Section: Introductionmentioning
confidence: 99%